Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.2136/sssaj2004.1386
|View full text |Cite
|
Sign up to set email alerts
|

Soil Hydraulic Properties Influenced by Stiff‐Stemmed Grass Hedge Systems

Abstract: The effectiveness of stiff‐stemmed grass hedge systems in controlling runoff and soil erosion is influenced by the water transport properties of the soil under grass hedge management. This study evaluated soil hydraulic properties within a grass hedge system 10 yr after establishment. The study was conducted at the USDA‐ARS research station near Treynor, IA in a field managed with switchgrass (Panicum virgatum) hedges. The soil was classified as Monona silt loam (fine‐silty, mixed, superactive, mesic Typic Hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 19 publications
10
80
0
2
Order By: Relevance
“…Soil water pressure data was used to estimate the effective pore size using the capillary rise equation (Jury et al 1991). Pore sizes were divided into four different classes: macropores (>1,000 μm [>0.039 in] effective diameter), coarse mesopores (60 to 1,000 μm [0.0024 to 0.039 in] effective diameter), fine mesopores (10 to 60 μm [0.00039 to 0.0024 in] effective diameter), and micropores (<10 μm [<0.00039 in] effective diameter) as were used in Rachman et al 2004.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil water pressure data was used to estimate the effective pore size using the capillary rise equation (Jury et al 1991). Pore sizes were divided into four different classes: macropores (>1,000 μm [>0.039 in] effective diameter), coarse mesopores (60 to 1,000 μm [0.0024 to 0.039 in] effective diameter), fine mesopores (10 to 60 μm [0.00039 to 0.0024 in] effective diameter), and micropores (<10 μm [<0.00039 in] effective diameter) as were used in Rachman et al 2004.…”
Section: Methodsmentioning
confidence: 99%
“…They also concluded that after six years of establishing the buffers, soil under buffers can store more water and hence would have lower runoff and less sediment, nutrient, and herbicide losses. Similarly, Rachman et al (2004) showed that areas under perennial grass hedges for more than ten years had lower bulk density and clay content and higher porosity and saturated hydraulic conductivity than areas under row crop cultivation for the same soil. Skaggs et al (2006) studied the effects of forest management on saturated hydraulic conductivity (K sat ) and found K sat values for a mature plantation forest were 20 to 30 times higher than values given in the soil survey for the study area.…”
mentioning
confidence: 90%
“…A few studies have suggested that planting switchgrass and other WSGs for bioenergy on sloping marginal lands not only provides cellulosic biomass but also improves ecosystem services such as reducing water erosion and improving soil and water quality, soil C sequestration, and biodiversity (Gilley et al, 2000;Rachman et al, 2004;Blanco-Canqui et al, 2014). Growing deep-rooted WSGs in fields with steep slopes can anchor and stabilize the soil while improving soil properties at deeper depths in the profile.…”
Section: Sloping Soilsmentioning
confidence: 99%
“…Saturated hydraulic conductivity and water infiltration rates are important to reducing runoff (Rachman et al 2004b;Gilley et al 2000) and soil bulk density is often reduced and macroporosity increased with soil under perennial grass (Rachman et al 2004a). Filters are expected to be relatively ineffective in cases of slow water infiltration such as with frozen, saturated, or compacted soils or soils of weak aggregation.…”
Section: All Runoff Eventsmentioning
confidence: 99%